Effect of alveolar bone support on zygomatic implants in an extra-sinus position—a finite element analysis study. Issue 6 (June 2015) - Freedman, M.; Ring, M.; Stassen, L.F.A.
Abstract The objective was to investigate the influence of maxillary alveolar bone on the stress distribution of zygomatic implants in an extra-sinus position. A three-dimensional finite element model was created based on a computed tomography scan of an edentulous female patient. Two zygomatic implants were modelled and placed in the skull in an extra-sinus position. These were supported by the zygomatic bone and the maxillary alveolar bone and were connected by a fixed bridge. This model was duplicated, and the area of the maxillary alveolar bone supporting the implants was removed. Occlusal and lateral forces were applied to both models and the maximum von Mises stresses were recorded. Higher maximum stresses were noted in the model with no alveolar support. Occlusal stresses were higher than lateral stresses in the model with no alveolar support, while occlusal stresses were lower than lateral stresses in the model with alveolar support. Low stresses were noted in the zygomatic bone in both models. Maxillary alveolar bone support is beneficial in the distribution of forces for zygomatic implants placed in an extra-sinus position.